Bacteriosis associated with epizootic in the giant sea perch, Lates calcarifer, and the estuarine grouper, Epinephelus tauvina, cage cultured in Malaysia - Nash, Gary; Anderson, Ian G.; Shariff, M.; Nor Shamsudin, Mariana (Elsevier, 1987)
A mass mortality in marine cage-reared adult sea perch, Lates calcarifer, and grouper, Epinephelus tauvina, offshore Kukup Laut, State of Johore, southern Peninsular Malaysia was investigated. The quantity and quality of trash fish fed to the fish was determined to be inadequate and the water quality was reduced during the northeast monsoon occurring at this time. Histologically, affected fish presenting extensive multiple skin lesions demonstrated severe haemorrhagic ulcerative dermatitis with additional changes in the internal organs consistent with a subacute septicaemia and an underlying malnutrition. Pseudomonas sp., probably Pseudomonas anguilliseptica, was identified as the agent responsible for the haemorrhagic septicaemia in the fish. With the end of the northeast monsoon, improved nutrition and water quality eliminated the problem in the adult fish, emphasizing the secondary opportunistic role of Pseudomonas and the importance of primary stresses such as that caused by suboptimal nutrition and environment in the initiation of disease in fish.